Business Strategy of CV Jaya Sampurna in Facing Soft Drink Distributor Competition in Bekasi - Seri Nurmala; Hartiwi Hartiwi (Binus Business Review, 2015)
CV Jaya Sampurna is a soft drink distributor in Bekasi. Distributor company has a low profit margin, moreover the product sold is Fast Moving Consumers Goods with a very low profit margin (3.5%–5%). Therefore the company depends on a high volume of sales. Besides, there are many competitors in this industry, thus the business strategy is needed to improve the competitive advantage of the company. Given the conditions,this research was to identify the internal and the external factors, to identify the formulation of business strategy alternative, and to identify the recommendation of functional strategy for CV Jaya Sampurna. Research used descriptive method; and the type of research used was case study. Data were gathered from questionnaires and interview to three member of managers: Director, Operational Manager, and Finance Manager. Data wereanalyzed by using EFE, IFE, SWOT, IE, Grand Strategy Matrix and QSPM. The result of this research implies that the alternative strategy based on QSPM’s result was market penetration